Halogenated Boroxine Dipotassium Trioxohydroxytetrafluorotriborate K2[B3O3F4OH] Inhibits Emerging Multidrug-Resistant and β-Lactamase-Producing Opportunistic Pathogens - Carev, Ivana (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Halogenated boroxine dipotassium trioxohydroxytetrafluorotriborate, K2[B3O3F4OH] was investigated for antimicrobial potential by targeting the multidrug-resistant opportunistic pathogens associated with skin and wound infections. The antimicrobial testing against eleven bacterial and four fungal species revealed good activity of boroxine against pathogenic filamentous fungi Penicillium funiculosum Thom and Aspergillus niger van Tieghem; moderate bioactivity against the yeast Candida albicans (C. P. Robin) Berkhout; the best antibacterial effect, stable over a 24-h period, was observed against the methicillin-resistant Staphylococcus aureus Ogston strain. The atomic force microscopy (AFM) used to investigate the morphology of S. aureus cells revealed indentations on its cell envelope after the boroxine exposure. These results show that in addition to the antitumor effect, boroxine exerts wide spectrum antimicrobial activity, thus may help preventing the development of skin and wound-related opportunistic infections.